PENGAJARAN DAN PEMBELAJARAN ASTRONOMI ISLAM DI MALAYSIA: SUATU PENGENALAN: THE TEACHING AND LEARNING ISLAMIC ASTRONOMY IN MALAYSIA: AN INTRODUCTION - Kamaruzaman, Nurul Nadhrah; Ahmadun, Musaiyadah; Jamil, Asyraf Isyraqi; Ali @ Mat Zin, Aizan (Journal of Islamic Educational Research, 2017)
The science of Islamic Astronomy or Falak began to receive its attention in Malaysia through the existence of some discussions related to the teaching and learning of the knowledge among Malaysian educational institutions. This paper aims to introduce the development of the field in Malaysian educational system through a systematic teaching and learning process. A qualitative approach is adopted which includes documentation method in collecting data process, and document analysis method in analysing data process. In general, there are some aspects related to the teaching and learning of Islamic Astronomy in Malaysia that are required to be enhanced, which also depict the presence of 'Islamic Transfer Knowledge Programme' as a symbol of Islamization of knowledge in the country.